2020
DOI: 10.3390/chemosensors8030062
|View full text |Cite
|
Sign up to set email alerts
|

Study on Ultrasonic Assisted Electrochemical Drill-Grinding of Superalloy

Abstract: Electrochemical grinding (ECG) technique composed of electrochemical machining (ECM) and mechanical grinding is a proper method for machining of difficult-to-cut alloys. This paper presents a new ultrasonic assisted electrochemical drill-grinding (UAECDG) technique which combines electrochemical drilling, mechanical grinding, and ultrasonic vibration to fabricating high-quality small holes on superalloy. By applying ultrasonic vibration to high-speed rotating electrode in ECG, machining stability, efficiency, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…Ultrasonic-assisted electrochemical grinding (UAECG) is a novel hybridized electrochemical grinding technology developed by combining ultrasonic vibration-assisted machining [ 3 , 4 ] and electrochemical grinding [ 5 , 6 ]. Compared with ordinary ECG, the UAECG process is more stable [ 7 ], the grinding force is smaller [ 5 , 7 ], the conductive grinding wheel wear is alleviated [ 5 ], and the machined surface roughness is reduced [ 5 , 7 , 8 , 9 ]. Therefore, with high-end equipment and precision machinery technology development, UAECG is receiving increasing attention and application in industry.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ultrasonic-assisted electrochemical grinding (UAECG) is a novel hybridized electrochemical grinding technology developed by combining ultrasonic vibration-assisted machining [ 3 , 4 ] and electrochemical grinding [ 5 , 6 ]. Compared with ordinary ECG, the UAECG process is more stable [ 7 ], the grinding force is smaller [ 5 , 7 ], the conductive grinding wheel wear is alleviated [ 5 ], and the machined surface roughness is reduced [ 5 , 7 , 8 , 9 ]. Therefore, with high-end equipment and precision machinery technology development, UAECG is receiving increasing attention and application in industry.…”
Section: Introductionmentioning
confidence: 99%
“…They studied the planar ultrasonic-assisted electrochemical mill-grinding of Ti-6Al-4V with a metal-bonded CBN grinding wheel of 1.8 mm in diameter. Liu et al [ 8 , 9 ] developed an ultrasonic-assisted electrochemical drill-grinding machine tool for dealing with the precision machining of small holes with a diameter of 1.8 mm. They studied the ultrasonic-assisted electrochemical drill-grinding of 304 stainless steel plates with a thickness of 0.5 mm using metal bonded diamond ball head grinding tools.…”
Section: Introductionmentioning
confidence: 99%
“…Through the experiment, it was found that the efficiency and precision of the special section tube micro-groove machining could be improved by using synchronous laser-assisted STEM. Huang et al [ 26 ] proposed the ultrasonic-assisted electrochemical drill-grinding technology to reduce the surface roughness of the hole sidewall of the nickel-based superalloys from Ra 0.99 to Ra 0.14 µm. The existing research found that the electrochemical mechanical machining process could not only ensure the machining accuracy but also improved the harmonic profile with high frequency.…”
Section: Introductionmentioning
confidence: 99%
“…Traditional ECG usually uses conductive grinding heads with abrasive grains for material removal 3 . In recent years, to further improve the processing quality, methods such as ultrasonic-assisted ECG 4 , 5 , electrochemical jet-assisted grinding 6 , dry electrochemical mechanical machining 7 , and abrasive-free electrochemical mechanical machining 8 have been developed, and the application of ECG in the processing of metals and semiconductor materials has been promoted by these methods. In addition, many scholars have tried to promote the matching effect of dissolution and grinding by improving the flow field distribution.…”
Section: Introductionmentioning
confidence: 99%